Cognitive remediation therapy modulates intrinsic neural activity in patients with major depression - Schneider, Isabella; Schmitgen, Mike; Bach, Claudia; Listunova, Lena; Kienzle, Johanna; Depping, Malte S.; Kubera, Katharina Maria; Roesch-Ely, Daniela; Wolf, Robert Christian (Psychological medicine, 2020)
BackgroundCognitive impairment is a core feature of major depressive disorder (MDD). Cognitive remediation may improve cognition in MDD, yet so far, the underlying neural mechanisms are unclear. This study investigated changes in intrinsic neural activity in MDD after a cognitive remediation trial.MethodsIn a longitudinal design, 20 patients with MDD and pronounced cognitive deficits and 18 healthy controls (HC) were examined using resting-state functional magnetic resonance imaging. MDD patients received structured cognitive remediation therapy (CRT) over 5 weeks. The whole-brain fractional amplitude of low-frequency fluctuations was computed before the first and after the last training session. Univariate methods were used to address regionally-specific effects, and a multivariate data analysis strategy was employed to investigate functional network strength (FNS).ResultsMDD patients significantly improved in cognitive function after CRT. Baseline comparisons revealed increased right caudate activity and reduced activity in the left frontal cortex, parietal lobule, insula, and precuneus in MDD compared to HC. In patients, reduced FNS was found in a bilateral prefrontal system at baseline (p < 0.05, uncorrected). In MDD, intrinsic neural activity increased in right inferior frontal gyrus after CRT (p < 0.05, small volume corrected). Left inferior parietal lobule, left insula, left precuneus, and right caudate activity showed associations with cognitive improvement (p < 0.05, uncorrected). Prefrontal network strength increased in patients after CRT, but this increase was not associated with improved cognitive performance.ConclusionsOur findings support the role of intrinsic neural activity of the prefrontal cortex as a possible mediator of cognitive improvement following CRT in MDD.
First published online: 16 September 2019
Gesehen am 16.07.2021